Influence of adeno-associated virus on adherence and growth properties of normal cells. - Bantel-Schaal, U (1992)
It has been shown previously that infection of newly established cell cultures from malignant human tumors with adeno-associated parvovirus type 2 or type 5 results in growth arrest and cell death. Here we report that the additionally observed antiproliferative effect on diploid human fibroblasts is transient and is connected to a reduced number of cells in S phase. Progression through the cell cycle is disturbed either in G0/G1 or at the G1/S boundary, but an additional arrest in G2 cannot be excluded. DNA synthesis and cell proliferation are resumed when cells are recultured after loosening of cell-matrix adhesions by trypsin treatment. In contrast, they are not resumed by solely providing growth factors via higher amounts of fetal calf serum. The results suggest that cell adherence is altered in adeno-associated parvovirus-infected human embryo fibroblasts.